![26)\; \; \dfrac{(x+2)(x-1)^2}{x-3}<0\\\\znaki:\; \; +++(-2)---(1)---(3)+++\\\\x\in (-2,1)\cup (1,3)\\\\naibolshee\; celoe:\; \; x=2 26)\; \; \dfrac{(x+2)(x-1)^2}{x-3}<0\\\\znaki:\; \; +++(-2)---(1)---(3)+++\\\\x\in (-2,1)\cup (1,3)\\\\naibolshee\; celoe:\; \; x=2](https://tex.z-dn.net/?f=26%29%5C%3B%20%5C%3B%20%5Cdfrac%7B%28x%2B2%29%28x-1%29%5E2%7D%7Bx-3%7D%3C0%5C%5C%5C%5Cznaki%3A%5C%3B%20%5C%3B%20%2B%2B%2B%28-2%29---%281%29---%283%29%2B%2B%2B%5C%5C%5C%5Cx%5Cin%20%28-2%2C1%29%5Ccup%20%281%2C3%29%5C%5C%5C%5Cnaibolshee%5C%3B%20celoe%3A%5C%3B%20%5C%3B%20x%3D2)
0\\\\Otvet:\; \; x=3\; ." alt="27)\; \; \sqrt{3+2x}=x\; \; ,\; \; ODZ:\; \; \left \{ {{3+2x\geq 0} \atop {x\geq 0}} \right. \; \; \to \; \; \; x\geq 0\\\\3+2x=x^2\\\\x^2-2x-3=0\; \; ,\; \; x_1=-1\; ,\; \; x_2=3\; \; \; (teorema\; Vieta)\\\\x_2=3>0\\\\Otvet:\; \; x=3\; ." align="absmiddle" class="latex-formula">